Efficacy of brentuximab vedotin combined with sintilimab in relapsed/refractory DLBCL patient with secondary hemophagocytic syndrome: a case report and literature review - Cheng, Siyu; Wu, Huihong; Bao, Wenguang; Peng, Zhigang; Huang, Fengxiang; Zhou, Shengsheng; Mo, Qinli; Li, Ye; Bin, Yehong; Lan, Dong; Yang, Haiyan (Frontiers in Oncology, 2025)
Currently, there is no definitive and effective treatment strategy for relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL). In recent years, studies on brentuximab vedotin (BV) and programmed cell death-1 (PD-1) monotherapy for R/R DLBCL have demonstrated significant clinical benefits. Based on this, this article retrospectively analyzes a case of R/R DLBCL with secondary hemophagocytic syndrome successfully treated with BV combined with a PD-1 monoclonal antibody and reviews the relevant literature. The patient was a 55-year-old woman who was diagnosed with stage IIE diffuse large B-cell lymphoma in June 2020. She failed to achieve complete remission during first-line treatment with the R-CHOP (rituximab, cyclophosphamide, doxorubicin/epirubicin, vincristine, and prednisone) regimen. After switching to the R2-GDP regimen for second-line salvage therapy, her condition continued to progress, and recurrent hemophagocytic syndrome developed. Subsequent treatment with BV combined with a PD-1 monoclonal antibody resulted in significant relief of her symptoms. As of the follow-up on 8 March 2025, the patient maintained a normal life and had no intolerable immune-related adverse effects. This study suggests that BV combined with PD-1 monoclonal antibody may exert a synergistic effect in the treatment of R/R DLBCL complicated with hemophagocytic lymphohistiocytosis (HLH).